Evaluation of Energy Conservation Measures and Greenhouse Gas Emission Reduction of Lighting System in Rattanakosin Place Building, Rajamangala University of Technology Rattanakosin - Pukdum, Jirasak; Amatayakul, Valee; Louchot, Waranyoo (Rajamangala University of Technology Tawan-ok Research Journal, 2025)
This study aims to evaluate energy savings and greenhouse gas (GHG) emission reductions achieved by replacing fluorescent lamps with LED lamps in the Rattanakosin Place Building at Rajamangala University of Technology Rattanakosin. Energy consumption data were collected before and after the replacement, along with analyses of Life Cycle Cost (LCCA), Return on Investment (ROI), and GHG mitigation. The findings reveal that replacing 964 fluorescent lamps (28W, 14W, and 11W) with LED lamps (18W, 9W, and 5W, respectively) reduced energy consumption by 48.8%, from 54,030.24 kWh/year to 27,609.12 kWh/year, and correspondingly decreased GHG emissions by 14,964.92 kgCO2eq/year (49%). Over a 3-year lifespan, LCCA showed the total cost of the LED system (486,013 THB) was lower than the fluorescent system (784,583 THB), yielding net savings of 298,570 THB. The ROI stood at 121.2% with a 10-month payback period, confirming economic viability. These results demonstrate positive impacts on environmental protection and national energy sustainability.